2017
DOI: 10.1177/0748233717737646
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of dietary omega-3 fatty acid supplementation on organophosphate poisoning

Abstract: In this study, we aimed to study the possible preventive effect of docosahexaenoic acid (DHA), a dietary omega-3 fatty acid, on toxicity caused by chlorpyrifos (CPF). Six groups of Sprague Dawley rats (200-250 g) consisting of equal numbers of males and females (n = 8) were assigned to study. The rats were orally given for 5 days. The control group was administered pure olive oil, which was the vehicle for CPF. The CPF challenge groups were administered oral physiological saline, pure olive oil, or DHA (50, 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…The present study showed that malathion induced oxidative stress which confirmed by the increase of serum MDA level and the decrease of CAT level. These findings are generally in agreement with previous experimental investigations on animals exposed to malathion and other pesticides (Avci et al, 2018;Selmi et al, 2018;Uchendu et al, 2018;Aboubakr et al, 2019;Jalili et al, 2019;Khalifa Alkhalf, 2019). MDA is an end product of lipid peroxidation, and therefore increased concentrations indicate an increase in reactive oxygen species (ROS) concentration and resulting oxidative damage.…”
Section: Discussionsupporting
confidence: 91%
“…The present study showed that malathion induced oxidative stress which confirmed by the increase of serum MDA level and the decrease of CAT level. These findings are generally in agreement with previous experimental investigations on animals exposed to malathion and other pesticides (Avci et al, 2018;Selmi et al, 2018;Uchendu et al, 2018;Aboubakr et al, 2019;Jalili et al, 2019;Khalifa Alkhalf, 2019). MDA is an end product of lipid peroxidation, and therefore increased concentrations indicate an increase in reactive oxygen species (ROS) concentration and resulting oxidative damage.…”
Section: Discussionsupporting
confidence: 91%
“…Exposure to GLY resulted in increased DHA in female fish, potentially impacting fatty acid metabolism. There is evidence that DHA reduces inflammatory and oxidative stress response [ 24 ] and liver fibrosis [ 25 ] in rats treated with the organophosphate chlorpyrifos or carbon tetrachloride, respectively. The enhancement of DHA and cat production in the liver of females exposed to GLY could be a possible mechanism to counteract GLY-induced hepatotoxicity and inflammation mediated by lifaf , cxcl8b.1 and interleukins.…”
Section: Discussionmentioning
confidence: 99%
“…This increase has been attributed to the overexpression of iNOS which potentiates the synthesis of NO in the brain tissue [44]. A decrease in GSH content and inhibition of GPx, GR, SOD, and CAT activities have been recorded in different models following CPF intoxication [7,45]. The antioxidant enzymes protect the cell against different free radicals generated, following the exposure to chemicals and environmental toxicants.…”
mentioning
confidence: 99%